Dizziness in Saudi Arabia: An epidemiologic study - Alharbi, Ahmad A.; Alshammari, Maryam E.; Albalwi, Abdulaziz A.; Ramadan, Majed M.; Alsharif, Doaa S.; Hafiz, Ammar E. (Frontiers in Neurology, 2023)
Dizziness is one of the most common and recurring complaints in adults presenting at the clinic. However, its prevalence in the population of the Kingdom of Saudi Arabia remains unclear. We aimed to examine the prevalence and correlates of dizziness in a large sample of the Saudi population. In this is cross-sectional study, we used an electronic survey, which was completed by 1,478 respondents, with a response rate of 84% across five regions of Saudi Arabia. The online survey was launched on the Qualtrics website and distributed via social media channels to obtain heterogeneous responses. The study included adults aged ≥18 years who resided in Saudi Arabia during data collection. We used t-test and chi-square test for descriptive analysis and multiple logistic regression model to assess prevalence and predictors of dizziness. More than half of the participants were aged between 26 years and 45 years (58.66%). Of the participants, 42.97% reported having dizziness at the time of taking the survey. Women were less likely than men to report dizziness (OR=0.65; CI, 0.49, 0.87; P=0.003). A description of the type of dizziness by age revealed that vertigo slightly decreased with age. Unclear vision with movement or blurry vision was common in young adults, whereas imbalance was common in older adults. A multiple regression model adjusted for demographic characteristics revealed a statistically significant association between dizziness and age group. Participants in the age group of 46-55 years were 1.83 times more likely to report dizziness compared to those aged >65 years (odds ratio=1.83; confidence interval, 0.62, 5.41; P=0.0009). We concluded that dizziness is a common complaint in Saudi Arabia. Future studies should elucidate the risk factors for and mechanisms of dizziness to help prevent falls and reduced quality of life.